Author's View:Kinase joins the chaperone club: Androgen-regulated kinome reveals choline kinase alpha as a potential drug target in prostate cancer. (3rd May 2016) - Asim, Mohammad; Massie, Charlie E.; Neal, David E.
ABSTRACT: To identify clinically relevant downstream effectors of androgen signaling, the androgen-regulated kinome was defined in prostate cancer (PCa). Within this study, choline kinase α (CHKA) was identified as an androgen receptor chaperone that is both a biomarker of progression and a potential therapeutic target for PCa.